Muslim midwives the craft of birthing in the premodern middle east - Gilʻadi, Avner 1947- (Cambridge studies in Islamic civilization, 2015)
This book reconstructs the role of midwives in medieval to early modern Islamic history through a careful reading of a wide range of classical and medieval Arabic sources. The author casts the midwife's social status in premodern Islam as a privileged position from which she could mediate between male authority in patriarchal society and female reproductive power within the family. This study also takes a broader historical view of midwifery in the Middle East by examining the tensions between learned medicine (male) and popular, medico-religious practices (female) from early Islam into the Ottoman period and addressing the confrontation between traditional midwifery and Western obstetrics in the first half of the nineteenth century.